In-situ investigation of crystallization and structural evolution of a metallic glass in three dimensions at nano-scale. (May 2020) - Chen, Bo; Diao, Jiecheng; Luo, Qiang; Rawle, Jonathan; Liu, Xianping; Nicklin, Chris; Shen, Jun; Robinson, Ian
Abstract: The crystallization behaviour of metallic glasses (MGs) has been investigated since the discovery of these important functional materials in order to optimize their synthesis procedures and improve their performances. Methods including powder X-ray diffraction and transmission electron microscopy are usually combined to characterize the crystalline structure in these "amorphous" materials. Until now, these methods, however, have failed to show the crystallization of individual crystals in three dimensions. In this work, in-situ Bragg coherent X-ray diffraction imaging (BCDI) reveals the growth and the strain variation of individual crystals in the Fe-based MGs during annealing. There is preferential growth along the surface of the MG sample particles during the crystal formation and fractal structure formation around the developing crystal surfaces; there is also strain relaxation happening from the inner parts to the surfaces of the developing crystals while cooling. The work leads to propose that during the crystallization of Fe-based MGs, the growth of the individual crystals follows a two-step procedure; and at higher temperature after the first crystallization period of the Fe-based MGs, the crystallization of α-Fe could be a competitive process between the growth of α-Fe crystals and the erosion from other elements. Graphical abstract: Unlabelled Image Highlights: The growth and strain variation of individual crystals in the Fe-based metallic glass during annealing were investigated. The crystal growth follows a two-step model with the growth of both the crystal core and fractal structure. There is preferential growth along the surface of specimen during the α-Fe crystal formation from the metallic glass. Growth stagnation and strain relaxation are observed in the grown crystals while cooling.